An Assessment of Ghana's Enacted Kindergarten Curriculum - Seidu Sofo; Eugene F. Asola; Reginald Ocansey (Sustainable Programs to Reduce Educational and Avocational Disadvantages (SPREAD), 2019)
Drawing on the policy enactment theory, the present study assessed the enacted kindergarten (KG) curriculum in Ghana. Participants were 101 kindergarten teachers in one district of the Upper West Region of Ghana. They completed the Kindergarten Enacted Curriculum Scale (KECS) once. The KECS included 13 items (KG1) and 17 items (KG2) that assessed the extent to which participants taught content in four subscales: literacy and numeracy (LN), psychosocial skills (PS), environmental studies (ES), and physical development (PD). Participants responded to items on a 4-point Likert scale as major focus (scored 3), minor focus (scored 2), touched on briefly (scored 1), and not taught (scored 0). Descriptive and inferential statistics were computed for the entire scale and for each subscale. Results indicated that most participants focused on the LN and ES subscales; with the most neglected content areas being the PS and PD subscales. Most KG1 teachers focused on LN (Listening/Speaking-97.7%), with the lowest percentage in PS (Getting Along/Others- 25.0%) and PD (Physical Exercise-29.5%). Similarly, KG2 teachers focused on ES (Healthy Individual-93.0%), and the lowest percentage in PS (Knowing/Living with Others-39.3%) and PD (Spatial Awareness-42.1%). PS was positively correlated with PD, ES, and KECS. Inferential tests revealed gender differences for the PD subscale. Data indicated grade level differences in teaching LN and PD. These findings suggest that kindergarten teachers in this study continued to focus on academics (LN and ES), despite the emphasis of the KG curriculum being on the holistic development of the young child.  Keywords: Assessment, curriculum, kindergarten, Ghana, teachers